EVALUASI PARTISIPASI SISWA DALAM PENGELOLAAN SAMPAH UNTUK MENDUKUNG PROGRAM SEKOLAH ADIWIYATA - Widiyaningrum, Priyantini; Lisdiana, Lisdiana; Purwantoyo, Eling (Indonesian Journal of Conservation, 2015)
This research was conducted in conjunction with the grant of IbM activities 2015 about waste management school. Partner program is SMAN 12 and SMAN 13 Semarang. The objective research was to describe implementation of activities, as well as to evaluating the level of student participation in waste management school. Respondents were determined by purposive. They are students members of the Scientific Work of Youth, which is involved in the implementation of this program. Each school was taken a sample of 50 students. Description of the implementation of the waste management program is presented in narrative.   Student participation was measured using (1) questionnaire to collect information about students participation in implementing the principles of the 3R waste management (reduce; reuse, recycle); and (2) multiple choice questions to gather information about the basic knowledge of the students to 3R waste management principles.  The data were tabulated and analyzed descriptively. The results showed that the program IbM in both partner schools already performing well, realizing home composting organic waste that can process at school. The existence of home composting to support Adiwiyata program. The level of student participation in school waste management is quite active with an average score of 164.67 (SMAN 12) and 168.33 (SMAN 13). Similarly, the level of students knowledge in waste management in the category enough with a score of 15.6 (SMAN 12) and 14.8 (SMAN 13). Penelitian ini dilaksanakan bersamaan dengan kegiatan hibah IbM  DIKTI tahun 2015 sebagai kelanjutan program sebelumnya. Mitra program adalah SMAN 12 dan SMAN 13 Semarang,  Tujuan penelitian untuk mendeskripsikan implementasi kegiatan, serta mengevaluasi sejauh mana tingkat partisipasi siswa dalam pengelolaan sampah sekolah. Responden ditentukan secara purposive, yaitu siswa anggota KIR (Karya Ilmiah Remaja) sekolah yang dilibatkan dalam pelaksanaan program, masing-masing sekolah sebanyak 50 siswa. Deskripsi implementasi program pengelolaan sampah disajikan secara naratif. Instrumen yang digunakan untuk mengukur partisipasi siswa terdiri dari (1) lembar kuesioner untuk mengumpulkan informasi sejauh mana partisipasi siswa dalam menerapkan prinsip 3R (reduce; reuse, dan recycle); (2) lembar pertanyaan multiple choice untuk mengetahui sejauh mana pengetahuan dasar yang dimiliki siswa terhadap prinsip 3R dalam pengelolaan sampah. Data kuantitatif yang terkumpul ditabulasi dan dianalisis secara deskriptif menggunakan acuan skala likert. Hasil penelitian menunjukkan bahwa program  IbM tahun 2014 dan 2015 di kedua sekolah mitra mencapai target yang ditetapkan yaitu mewujudkan rumah kompos yang mampu mengolah sampah organik sekolah dan mendukung program sekolah Adiwiyata. Tingkat partisipasi siswa dalam pengelolaan sampah sekolah tergolong cukup aktif dengan skor-rata-rata  164,67 (SMAN 12) dan 168,33 (SMAN 13).  Demikian pula tingkat pengetahuan siswa dalam mengelola sampah  masuk kategori cukup  dengan skor  15,6 (SMAN 12) dan 14,8 (SMAN 13).